The numerical distance effect is task dependent. - Goldfarb, Liat; Henik, Avishai; Rubinsten, Orly; Bloch-David, Yafit; Gertner, Limor (Memory & Cognition, 2011)
Number comparison tasks produce a distance effect e.g., Moyer & Landauer (Nature 215: 1519-1520, ). It has been suggested that this effect supports the existence of semantic mental representations of numbers. In a matching task, a distance effect also appears, which suggests that the effect has an automatic semantic component. Recently, Cohen (Psychonomic Bulletin & Review 16: 332-336, ) suggested that in both automatic and intentional tasks, the distance effect might reflect not a semantic number representation, but a physical similarity between digits. The present article (1) compares the distance effect in the automatic matching task with that in the intentional number comparison task and suggests that, in the latter, the distance effect does include an additional semantic component; and (2) indicates that the distance effect in the standard automatic matching task is questionable and that its appearance in previous matching tasks was based on the specific analysis and design that were applied.